Como você verifica a identidade # (csctheta-cottheta) (csctheta + cottheta) = 1 #?

Como voc├¬ verifica a identidade # (csctheta-cottheta) (csctheta + cottheta) = 1 #? N├│s temos: #(csc(theta) – cot(theta)) (csc(theta) + cot(theta))# Vamos expandir os par├¬nteses: #= (csc(theta)) (csc(theta)) + (csc(theta)) (cot(theta)) + ( – cot(theta) (csc(theta)) + (- cot(theta)) (cot(theta))# #= csc^(2)(theta) + csc(theta) cot (theta) – csc(theta) cot(theta) – cot^(2)(theta)# #csc^(2)(theta) – cot^(2)(theta)# Ent├úo, … Ler mais